2018
DOI: 10.1063/1.5039347
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of outer-midplane collector probes with isotopically enriched tungsten tracer particles for impurity transport studies in the scrape-off layer of DIII-D (invited)

Abstract: Triplet sets of replaceable graphite rod collector probes (CPs), each with collection surfaces on opposing faces and oriented normal to the magnetic field, were inserted at the outboard mid-plane of DIII-D to study divertor tungsten (W) transport in the Scrape-Off Layer (SOL). Each CP collects particles along field lines with different parallel sampling lengths (determined by the rod diameters and SOL transport) giving radial profiles from the main wall inward to R-Rsep ∼ 6 cm. The CPs were deployed in a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The 2016 DIII-D Metal Rings Campaign (MRC) represented the first large-scale use of high-Z plasma facing components (PFCs) in DIII-D. The hardware and diagnostic tools developed for the MRC have been described in previous works [40][41][42] and are only briefly re-described here. As shown in figure 4(a), two toroidally symmetric rings of isotopically distinct W-coated tiles were installed in the DIII-D lower, outer divertor.…”
Section: Experimental Setup: the Diii-d Tokamakmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2016 DIII-D Metal Rings Campaign (MRC) represented the first large-scale use of high-Z plasma facing components (PFCs) in DIII-D. The hardware and diagnostic tools developed for the MRC have been described in previous works [40][41][42] and are only briefly re-described here. As shown in figure 4(a), two toroidally symmetric rings of isotopically distinct W-coated tiles were installed in the DIII-D lower, outer divertor.…”
Section: Experimental Setup: the Diii-d Tokamakmentioning
confidence: 99%
“…Two sight lines for a new UV survey spectroscopy (200-400 nm) diagnostic were also installed, allowing for real-time monitoring of a number of WI and WII spectral lines [44]. Sets of graphite rods were installed close to the outboard midplane in the far SOL as collector probes to measure the fluence of tungsten in the far-SOL [41], similar to the approach on ASDEX-Upgrade [45]. Two new Langmuir probes (LPs) were installed at the major radius of the shelf ring, which in addition to the existing LP array and Divertor Thomson Scattering (DTS) system, allowed for detailed characterization of the divertor and SOL background plasmas during MRC experiments.…”
Section: Experimental Setup: the Diii-d Tokamakmentioning
confidence: 99%
“…To this end, DIII-D executed the MRC where two rings of toroidally symmetric, isotopically distinct W-coated tiles were installed in the lower, outer divertor, figure 1 [25]. Double-sided graphite CPs were inserted at the OMP on the MiMES reciprocating drive [26,27] where they remained for a set number of discharges. To avoid re-erosion of deposits on the CPs, they were inserted no deeper than to ∼7 cm outside the separatrix and were connected along field lines that limited on protruding regions of the vessel wall, placing them in what is defined as the wall-SOL [28], see figure 1.…”
Section: Experimental Setup: Similar Discharges Differing Primarily I...mentioning
confidence: 99%
“…Studies have already shown the valuable insights to SOL impurity transport/leakage provided by CPs during MRC. In [26,30] it is shown that by using the LAMS data and a stable isotope mixing model (SIMM), the fractional contribution from each W ring to the total W measured on each CP could be measured. The potential effect of the strength of radial transport on the asymmetry in total deposited W between the two CP sides is shown in [27].…”
Section: Experimental Setup: Similar Discharges Differing Primarily I...mentioning
confidence: 99%
See 1 more Smart Citation